Analysis of clay and Mn deposits from the Pacific - Seth Krishnaswami (PANGAEA, 1976)
The concentrations of Sc, Ti, Fe, Mn, Co, Ni, Cu, La, Th and U have been measured in several Pacific pelagic clays having widely different accumulation rates, 0.4-9.0 mm/103 yr. The authigenic fractions and deposition rates of these elements have been estimated from the measured concentrations using various models. The results show that in Pacific clays about 90% Mn, 80% Co and Ni and 50% Cu are authigenic whereas the major fraction (>90%) of Sc, Ti, Fe, La, Th and U are of detrital origin. Anticorrelation between the clay accumulation rates and the concentrations of Mn, Co, Ni and Cu is observed. This suggests a uniform authigenic deposition of these elements superimposed on varying amounts of detrital materials. The concentrations of Sc, Ti and Th are almost independent of sedimentation rates, indicating that their authigenic deposition is small compared to their detrital contribution. Comparison of the authigenic deposition and river input rates shows that Mn, Co and Ni are accumulating in excess of their supply by factors of 2-10, whereas the converse is true for Cu and U. Additional sources to account for the budgetary discrepancies of Mn, Co and Ni are discussed, with particular reference to in situ leaching of detrital phases transported to the oceans via rivers.
Supplement to: Krishnaswami, S (1976): Authigenic transition elements in Pacific pelagic clays. Geochimica et Cosmochimica Acta, 40(4), 425-434, https://doi.org/10.1016/0016-7037(76)90007-7